Time-dependent mortality and behavioral response of Odontotermes obesus (Blattodea: Termitidae) against different dose rates of pesticides for sustainable forest management - Aslam, Asad; Chi, De-Fu; Abbasi, Asim; Arshad, Muhammad; Hafeez, Faisal; Fayyaz, Amna; Hatamleh, Ashraf Atef; Abdullah Al-Dosary, Munirah (Frontiers in Forests and Global Change, 2023)
Termites have become a global concern and its effective management remained a challenge since time immemorial. Certain microbial and botanical agents have been used for its management but their efficacy has been compromised particularly in field conditions. Hence, the current study was designed to check the efficacy of low doses of different pesticides such as chlorpyrifos, fipronil, bifenthrin and Chlorantraniliprole against mortality and behavioral responses of O. obesus at two different temperature ranges (16 ± 1 and 26 ± 1 °C). The discrete behavioral symptoms included intoxication, ataxia, and moribundity and death. Laboratory maintained termite workers were exposed to different concentrations of pesticides through a filter paper bioassay. All tested pesticides and their concentrations differed significantly regarding their lethal time (LT50) values against the mortality of termite workers. Moreover, the LT50 values of pesticides gradually decreased with increased pesticidal concentrations. Temperature also had a significant effect on the efficacy of tested pesticides as all pesticides showed better results at higher temperature range. At both tested temperatures, Chlorantraniliprole (5 ppm) proved to be the most effective pesticide against termite workers. Similarly, the behavioral symptoms also varied depending on pesticides and their administered concentrations and existed for a relatively longer time span at lower temperature. In most of cases, the order of responses was moribundity followed by intoxication, and ataxia. Moribundity and intoxication were the most frequently observed symptoms for Chlorpyriphos and Bifenthrin treated termite workers. This is a provisional file, not the final typeset article In case of Fipronil, intoxication was the most pronounced symptoms. Similarly, maximum value of ataxia was recorded in case of Chlorantraniliprole. However, moribund symptoms lasted longer in all tested concentrations of Chlorantraniliprole followed by ataxia and intoxication. The overall order of toxicity was chlorantraniliprole > bifenthrin > fipronil > chlorpyrifos. These pesticides at their low doses did not exhibit any repellent action nor detected by the foraging termite workers. Moreover, their relatively slow action mechanism makes them a suitable candidate for infecting whole colony away from treated surface.